2021
DOI: 10.1177/20563051211036385
|View full text |Cite
|
Sign up to set email alerts
|

What is the “lite” in “alt-lite?” The discourse of white vulnerability and dominance among YouTube’s reactionaries

Abstract: This article examines the discourse of “alt-lite” YouTube personalities in a North American context, with a focus on how whiteness is understood and represented. It argues that, despite their self-presentation as color-blind conservatives, these figures are firmly embedded within white supremacist ideology. A qualitative approach to content analysis is adopted to excavate the logics underlying these videos and to highlight the rhetorical tools at work. By framing themselves as the vulnerable targets of progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
0
11
0
5
Order By: Relevance
“…Some alt-lite groups have participated in acts of racially or ethnically motivated violent extremism, often based on anti-Black Lives Matter (BLM), anti-Muslim, anti-Semitic, or anti-immigrant platforms, while some alt-lite groups have participated in other forms of domestic terrorism (ADL, 2017b). Further, racially and ethnically heterogenous REMVE actors were significant for this study because they might use different or more-coded language than traditional white supremacist groups use (Ma, 2021).…”
Section: Equity-related Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some alt-lite groups have participated in acts of racially or ethnically motivated violent extremism, often based on anti-Black Lives Matter (BLM), anti-Muslim, anti-Semitic, or anti-immigrant platforms, while some alt-lite groups have participated in other forms of domestic terrorism (ADL, 2017b). Further, racially and ethnically heterogenous REMVE actors were significant for this study because they might use different or more-coded language than traditional white supremacist groups use (Ma, 2021).…”
Section: Equity-related Considerationsmentioning
confidence: 99%
“…Per our review of the relevant literature from such entities as ADL, the Southern Poverty Law Center, the Center for Strategic and International Studies (CSIS), academic journals, and news reports, we identified REMVE groups proclaiming a colorblind ideology to include the Proud Boys, Patriot Prayer, the Oath Keepers, and the Fraternal Order of Alt-Knights. Common terms used on social media that differ from those in traditional alt-right and whitesupremacist groups included western chauvinism, corporate globalist left, Judeo-Christian values, race-baiters, MLK (presumably for Martin Luther King, Jr.), manosphere, venerate the housewife, west is the best, RWDS, and Pinochet did nothing wrong (see ADL, 2017b; Center for Extremism, 2018; Coaston, 2020;Gupta, 2018;Hermann, 2020;Ma, 2021;McQueen, 2021;Miller, 2018;Ngangura, 2021;Southern Poverty Law Center, undated;Trouillard, 2021; and "Understanding Multiracial Whiteness and Trump Supporters," 2021). To ensure equity of analysis and avoid bias, we included several of these terms (manosphere, western chauvinism, venerate the housewife, RWDS, and Pinochet was right) in our analysis on term emergence discussed in Chapter Three and intend to include terms from more-diverse REMVE actors in our validation of the RVE-Flock tool going forward.…”
Section: Equity-related Considerationsmentioning
confidence: 99%
“…As Hartzell (2018) argues, Spencer’s website focused on “arguing for the importance of embracing pro-white racial consciousness” (p. 19). Building on the legacy of white supremacist organizing throughout the 20th century, the “alt-right” embraces a “victim ideology” that frames advancements won by Black people, and other people of color, as discriminatory attacks on the rights of white Americans (Berbrier, 2000; Ma, 2021). They also claim, baselessly, that the white race itself is endangered due to low white birth-rates, miscegenation laws, and high rates of non-white immigration.…”
Section: Background and Rationalementioning
confidence: 99%
“…The connections between networked online communication and far-right organizing have been the subject of considerable scholarship over the past two decades (Daniels, 2009;Donovan, 2019;Munn, 2019;Phillips, 2015;Whine, 2003). This research has shown how white supremacist and other reactionary groups have adopted new technologies "to amplify, monetize, and mask their ideologies" (Ma, 2021; see also Ganesh, 2020;Massanari, 2017). In this way, white supremacists act as "innovation opportunists," who exploit platform affordances, legislative loopholes, and moderation blind spots to advance their ideological goals (Daniels, 2018).…”
Section: The Far-right Onlinementioning
confidence: 99%
See 1 more Smart Citation